2012
DOI: 10.1128/aem.07253-11
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Methyl tert -Butyl Ether-Degrading Microorganisms Identified in Wastewater Treatment Plant Samples by Stable Isotope Probing

Abstract: ABSTRACTAnaerobic methyltert-butyl ether (MTBE) degradation potential was investigated in samples from a range of sources. From these 22 experimental variations, only one source (from wastewater treatment plant samples) exhibited MTBE degradation. These microcosms were methanogenic and were subjected to DNA-based stable isotope probing (SIP) targeted to both bacteria and archaea to identify the putative MTBE degraders. For this purpose, DNA was extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 70 publications
0
19
0
1
Order By: Relevance
“…T-RFLP fingerprinting of densityresolved DNA fractions was done with primers 27F-FAM (5 -AGAGTTTGATCMTGGCTCAG-3 , 5 end-labeled with carboxyfluorescein) and 1492R (5 -GGTTACCTTGTTACGACTT-3 ) for bacteria and A109F-FAM (5 -ACKGCTCAGTAACACGT-3 , 5 end-labeled with carboxyfluorescein) and A934R (5 -GTGCTCCCCCGCCAATTCCT-3 ) for archaea; the purified PCR products were digested with HaeIII, AluI and RsaI (New England Biolabs) and the data were analyzed with GeneScan software, all as described previously [39][40][41].…”
Section: Experiments For Pcr T-rflp 16s Rrna Gene Sequencing and Qpcrmentioning
confidence: 99%
“…T-RFLP fingerprinting of densityresolved DNA fractions was done with primers 27F-FAM (5 -AGAGTTTGATCMTGGCTCAG-3 , 5 end-labeled with carboxyfluorescein) and 1492R (5 -GGTTACCTTGTTACGACTT-3 ) for bacteria and A109F-FAM (5 -ACKGCTCAGTAACACGT-3 , 5 end-labeled with carboxyfluorescein) and A934R (5 -GTGCTCCCCCGCCAATTCCT-3 ) for archaea; the purified PCR products were digested with HaeIII, AluI and RsaI (New England Biolabs) and the data were analyzed with GeneScan software, all as described previously [39][40][41].…”
Section: Experiments For Pcr T-rflp 16s Rrna Gene Sequencing and Qpcrmentioning
confidence: 99%
“…In a DNA-SIP study of MTBE degradation in methanogenic microcosms, 18 clones enriched with 13C were related to Sphingopyxis of the Sphingomonadaceae family (Sun et al 2012). The Sphingomonas genus in this family has also been associated with MTBE degradation.…”
Section: Resultsmentioning
confidence: 99%
“…Historically, mixed results have been obtained in studies of anaerobic ether oxygenate and tertiary alcohol biodegradation [2] and this trend has continued to the present. In some recent studies, little or no biodegradation has been observed over long periods [3,4]. In other cases, rapid anaerobic biodegradation has been observed [5].…”
Section: Anaerobic Biodegradation Of Ethers Oxygenatesmentioning
confidence: 99%
“…A laboratory-based 13 C-DNA-stable isotope probing study recently identified Firmicutes as well as Sphigopyxis strains as dominant MTBE-degrading organisms in methanogenic wastewater treatment plant samples [4]. A study using 13 C 4 -TBA has also characterized aerobic TBA-metabolizing strains in Bio-GAC reactor samples.…”
Section: Stable Isotope Studies Of Mtbe Oxidationmentioning
confidence: 99%